Bar Retained Tooth Supported Overdenture: A Case Report - Bista, S; Sapkota, B (Journal of Nepalese Prosthodontic Society, 2022)
Overdenture helps in preservation of the sensation of proprioception, maintains the border seal and provides the patient with good phonetics and chewing efficiency. The retention and stability of such prosthesis is enhanced greatly in bar-supported overdentures. This case report presents the step by step procedure for the fabrication of a canine supported hader bar mandibular overdenture that opposes a conventional complete maxillary denture. The bar was fabricated from pre-formed plastic bar, casted and female clips were attached in the mandibular denture. The mode of retention was primarily through frictional resistance.